The Scope, Applications, and Future of Artificial Intelligence in Instructional Design - Sürmelioğlu, Yeşim; Arslankara, Veysel Bilal; Alp, Mustafa (IGI Global Scientific Publishing, 2025)
This chapter examines the role, applications, and future potential of artificial intelligence (AI) in instructional design. It begins by addressing the rise of AI in education and its intersection with instructional design. The integration of AI with established instructional design models is discussed, alongside an exploration of how AI aligns with various learning theories. The chapter explores AI-driven instructional design applications ranging from personalized learning systems to adaptive learning platforms. It illustrates, with examples, how automated feedback and assessment systems can reduce teachers' workloads while enhancing students' educational experiences. Ethical concerns and challenges encountered during the transformative process of AI in education are also addressed. In conclusion, AI is considered a powerful tool with the potential to make instructional design more personalized, data-driven, and effective. In the future, the role of AI in education is likely to expand further, reshaping instructional processes across diverse educational contexts.